PENGARUH MANAJEMEN PENGENDALIAN MATERIAL DALAM MENCEGAH DAN MENGATASI KETERLAMBATAN PROYEK BANGUNAN DI MADRASAH ALIYAH KEJURUAN (MAK) ROKAN HULU - Husnah Husnah; doni rinaldi basri (LPPM Universitas Abdurrab, 2017)
Material requirements planning requires information that can support the project activities so that the linkage of supply and use of materials to a work can proceed smoothly and delayed ordering schedule which may cause increased costs to the project as much as may not occur. Given the magnitude of losses caused by material delays, and with the discovery of material factors as one of the factors causing delays in building projects that are quite dominant, it is necessary to attempt to prevent delay factors due to the material. The purpose of this research is to know the ranking (ranking) item of material control program in preventing and overcoming the delay. In this study using a survey with a questionnaire tool which is the main thing for data collection. The results of questionnaires are incarnate in numbers, tables, descriptions and conclusions. By asking written questions about the material control program of building construction projects to the respondents. Prior to filling out the questionnaire, the purpose and objectives of the study were first explained to the respondents. The result of this research is obtained by material control program to prevent delay which is Control Schedule plan of material use for each work item and how to overcome the delay in the way when the delay occurs because Supplier experience something, then use Supplier backup.